Kejanggalan Beberapa Putusan Korupsi Pengadaan dan Kaitannya dengan Konstitusi - Wibowo, Richo Andi (Mahkamah Konstitusi Republik Indonesia, 2016)
This paper aims at highlighting some odd court decisions on corruption typed “state financial loss” in public procurement sector. It is odd because of the following reasons: (i) the nature of the case is more about administrative or private law instead of criminal law; (ii) some consider that it will be unjust to sentence guilty the accused; (iii) the cases ensnare persons who are perceived as reformist and clean. The first point will be the focus of elaboration. It will be argued that the encroachment of criminal law towards the area of administrative and private laws are caused by the lower standard of proof for the corruption typed “state financial loss”. Currently, the applied standard is “more likely than not” instead of “beyond reasonable doubt”. The situation which some people are jailed while their faults are more about administrative and private is a justice issue. As the upright of justice is the mandate of the constitution, therefore, articles that create this injustice (Article 2 section (1) and Article 3 of the Eradication Corruption Act) should be re-reviewed by the Constitutional Court. Although the court has previously reviewed the Articles and, therefore, this should be seen as a final and binding; this paper will give some arguments which explain the needs for the court to re-settle this matter.